1994
DOI: 10.1093/oxfordjournals.jbchem.a124535
|View full text |Cite
|
Sign up to set email alerts
|

3-Phosphohistidine/6-Phospholysine Phosphatase from Rat Brain as Acid Phosphatase1

Abstract: A phosphatase hydrolyzing 3-phosphohistidine and 6-phospholysine was purified from rat brain cytosol to 90% homogeneity on polyacrylamide gel electrophoresis in the presence of sodium dodecyl sulfate. One milligram of protein of the purified phosphatase released inorganic phosphate from 3-phosphohistidine, 6-phospholysine, AMP, GMP, and p-nitrophenyl phosphate at velocities of 6.5, 15.6, 15.0, 6.9, and 8.3 mumol/min, respectively. However, the purified enzyme could not hydrolyze N omega-phosphoarginine and pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Ohmori et al [47,48] reported the presence of two phosphatases in rat brain, one of which catalyses the hydrolysis of phospholysine, but not N3-phosphohistidine (PLPase; 30 kDa) whilst the other catalyses the hydrolysis of both phospholysine and N3-phosphohistidine (PHLPase; 150 kDa). Both enzymes do not catalyse the hydrolysis of phosphoarginine or phosphocreatine [47].…”
Section: Phospholysine Phosphatasesmentioning
confidence: 99%
“…Ohmori et al [47,48] reported the presence of two phosphatases in rat brain, one of which catalyses the hydrolysis of phospholysine, but not N3-phosphohistidine (PLPase; 30 kDa) whilst the other catalyses the hydrolysis of both phospholysine and N3-phosphohistidine (PHLPase; 150 kDa). Both enzymes do not catalyse the hydrolysis of phosphoarginine or phosphocreatine [47].…”
Section: Phospholysine Phosphatasesmentioning
confidence: 99%
“…These were shown to have inorganic pyrophosphatase, phosphohistidine and phospholysine activities [47][48][49]. Two further broad spectrum phospholysine phosphatases, 30 and 150 kDa, have been isolated from rat brain [50,51]. The 30-kDa, unlike the 150-kDa phosphatase, shows greater specificity towards phospholysine, not being capable of catalysing hydrolysis of phosphohistidine, phosphoarginine, phosphocreatine or any phosphoesters [50].…”
Section: Polyphosphorylation Targets Lysine Residuesmentioning
confidence: 99%
“…42 In addition, pHis phosphatase activity has been reported in rat tissue extracts but these have not been fully characterized. [43][44][45][46] Not only is His phosphorylation predicted to be prevalent in eukaryotic proteins, 38 it has also been associated with important mammalian cellular processes. For example, pHis has been shown to be present in heteromeric G proteins (GNB1), which are involved in G protein signalling, 15,47,48 KCa3.1 potassium channel, which is involved in ion conductance, 18,49 ATP-citrate lyase (ACLY), which is involved in cell metabolism, 9 histone H4, which is involved in chromatin biology, 21,22,28 transient receptor potentialvanilloid-5 (TRPV5), which regulates urinary Ca 2+ excretion, 17 and phosphoglycerate mutase 1 (PGAM1), which is involved in glycolysis.…”
mentioning
confidence: 99%